Elite Interests and Public Expenditure in Education in the late XIX and early XX Century in Prussia: A Dialogue Between History and Economics - Acosta Madiedo Aranzalez, Sebastian Enrique (Tiempo y economía, 2022)
This paper discusses how Prussia’s public education policy was intentionally guided by economic principles that modern economists have formalized and modeled. The essay compares the results of two economic models with the intentions held by Prussian government officials, which are enshrined in the research agenda of historians and academics. The paper concludes that Prussia’s public education policy was intuitively and intentionally influenced by economic principles and intuitions of the theoretical and empirical models chosen.